Numerical electromagnetic field analysis of archorn voltages during a back-flashover on a 500-kV twin-circuit line. - Mozumi, T. (IEEE Transactions on power delivery)
Archorn voltages of a simulated 500-kV twin-circuit line, in the case of one-phase back-flashover due to lightning to a tower top, are analyzed by the thin-wire time-domain analysis (TWTDA) code. Prior to this analysis, a recently proposed flashover model is incorporated into TWTDA. It becomes clear that the archorn voltages of the other two phases show a quite similar time-varying characteristic after one-phase back-flashover. An EMTP simulation is also carried out. The archorn voltages computed by the electromagnetic transients program (EMTP) agree well with those computed by TWTDA before the back-flashover on one phase. On the other hand, during about 1 μs after the one-phase back-flashover, the archorn voltages of the other two phases computed by EMTP deviate much from those computed by TWTDA. Particularly in the case of the middle- or the lower-phase back-flashover, the deviation is noticeable. The reason for this discrepancy is discussed.